Ultralow Ru-assisted and vanadium-doped flower-like CoP/Ni2P heterostructure for efficient water splitting in alkali and seawater. Issue 47 (24th November 2021) - Ma, Qianli; Jin, Huihui; Xia, Fanjie; Xu, Hanwen; Zhu, Jiawei; Qin, Rui; Bai, Huawei; Shuai, Binbin; Huang, Wenyang; Chen, Ding; Li, Zilan; Wu, Jinsong; et al.
Abstract : Flower-like RuV–CoNiP, with unique charge distribution and surface properties, effectively drives water splitting in alkali and seawater. Abstract : Low-cost high-performance catalysts are urgently required for hydrogen production from electrochemical water electrolysis by the hydrogen evolution reaction (HER) and slow oxygen evolution reaction (OER). Herein, by means of phosphating CoV-LDH impregnated with Ru (Ru–CoV-LDH/NF), a vanadium (V)-doped flower-like CoP/Ni2 P heterostructure coupled with ultralow Ru (RuV–CoNiP/NF) is constructed. The electronic modulation caused by V doping effectively stimulates the activity of the CoP/Ni2 P heterostructure assisted by ultrasmall Ru nanoparticles, thus the formed RuV–CoNiP/NF effectively drives the HER ( η 10 = 28 mV) and OER ( η 20 = 214 mV) in alkaline media. Impressively, during the overall water decomposition, it requires only an overpotential of 1.469 V to achieve 10 mA cm −2, demonstrating almost the most remarkable catalytic performance compared to the past literature. Notably, the catalyst can still positively promote the electrolysis of alkaline seawater: when achieving 20 mA cm −2, the required overpotential is only 1.538 V, which is almost the best experimental result at present. This work provides an idea for achieving low-cost high-performance bifunctional catalysts toward hydrogen production from water and seawater splitting.